2006
DOI: 10.11646/zootaxa.1338.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the leafhopper tribe Krisnini (Hemiptera: Cicadellidae: Iassinae) of the Indian subcontinent

Abstract: Two genera of the leafhopper tribe Krisnini, Gessius Distant & Krisna Kirkaldy, that occur in the Indian subcontinent, are redefined and a key to separate them is provided. Gessius verticalis Distant is redescribed. Eleven species of Krisna, including eight new species [namely: K. bakeri sp. nov. (Nepal: Katmandu, India: Uttaranchal), K. burmanica (Myanmar), K. delta sp. nov. (Nepal), K. megha sp. nov. (India: Assam, Meghalaya), K. raja sp. nov. (India: Kerala), K. varia sp. nov. (India: Karnataka, Kerala,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…These groups were defined by the structures of the male genitalia with the picturata group having a well‐defined sclerite between the connective and the base of the aedeagus, the clava group lacking this sclerite and having the preatrium extended ventrocaudally and the pruthii group lacking both the sclerite and the ventrocaudal extension of the preatrium. Viraktamath (1998) regarded C. contempta as fitting within his picturata group and this is supported here.…”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations
“…These groups were defined by the structures of the male genitalia with the picturata group having a well‐defined sclerite between the connective and the base of the aedeagus, the clava group lacking this sclerite and having the preatrium extended ventrocaudally and the pruthii group lacking both the sclerite and the ventrocaudal extension of the preatrium. Viraktamath (1998) regarded C. contempta as fitting within his picturata group and this is supported here.…”
Section: Introductionsupporting
confidence: 76%
“…This study has revealed that Exitianellus elegantula Evans (1966), the only described species of that genus, fits within Viraktamath's (1998) clava group of the genus Carvaka thereby creating a synonymy between Exitianellus and Carvaka . This also requires the transfer of E. elegantula from the Deltocephalinae: Athysanini to the Selenocephalinae: Paraboloponini.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Some authors (Linnavuori & Al-Ne'amy, 1983;Zhang & Webb, 1996;Viraktamath, 1998) treat these two groups as tribes of Selenocephalinae. Although previous authors considered Selenocephalini as a tribe of Deltocephalinae, Linnavuori & Al-Ne'amy (1983) created a separate subfamily Selenocephalinae with 7 tribes, including Selenocephalini Fieber, 1872 (formerly placed in Deltocephalinae), Drabescini Ishihara, 1953 (described as a separate family), Paraboloponini Ishihara, 1953 (described as a separate family) (= Bhatiini Linnavuori & Al-Ne'amy, 1983), Ianeirini Linnavuori, 1978 (formerly placed in Drabescinae), and 3 newly described tribes: Adamiini Linnavuori & AI-Ne'amy, 1983, Dwightiini Linnavuori & Al-Ne'amy, 1983, and Hypacostemmini Linnavuori & Al-Ne'amy, 1983 The main characters they used to define Selenocephalinae were: fore margin of head with transverse carinae, presence of antennalledges, specific shape of tentorial arms, and strigate microsculpture of first valvulae of female ovipositor.…”
Section: Introductionmentioning
confidence: 99%